ASSOCIATION BETWEEN ANEMIA LITERACY AND ANEMIA AMONG PREGNANT WOMEN: A CROSS-SECTIONAL STUDY AT AN INDEPENDENT MIDWIFERY PRACTICE IN INDONESIA - Latifah Hanum; Rita Sri Kurniawati; Dewi Rakhmawati; Khoirul Anam (Universitas Kusuma Husada Surakarta, 2026)
Background: Anemia in pregnant women remains a prevalent health issue and contributes to an increased risk of maternal and neonatal complications. One factor suspected to play a role is low anemia literacy, which affects pregnant women's ability to understand health information and make decisions about anemia prevention. Low literacy can lead to poor adherence to iron supplementation and suboptimal dietary patterns, particularly in iron intake. This study aims to analyze the relationship between anemia literacy and the incidence of anemia among pregnant women at TPMB Cindy Yosy.Methods: This study employed a correlational analytical design with a cross-sectional approach. The research sample consisted of 31 pregnant women selected using a total sampling technique. Data were collected using a validated 20–item questionnaire to measure anemia literacy and hemoglobin level examinations to determine anemia status. The methodology section briefly specifies that the instrument was validated and ethical approval was obtained. Data analysis was conducted using the Spearman Rho test.Results: Most respondents had poor anemia literacy (77.4%) and the majority experienced mild anemia (87.1%). The Spearman Rho test yielded a p-value = 0.000 (<0.05) with a correlation coefficient (rs) = +1.000, indicating a positive association with a very strong correlation between anemia literacy and the incidence of anemia in this sample distribution, which requires cautious interpretation.Conclusion: There is a significant association between anemia literacy and the incidence of anemia in pregnant women. Lower anemia literacy is associated with a higher incidence of anemia in pregnant women.